2020
DOI: 10.3892/ol.2020.11965
|View full text |Cite
|
Sign up to set email alerts
|

An increase of microRNA‑16‑1 is associated with the high proliferation of squamous intraepithelial lesions in the presence of the integrated state of HR‑HPV in liquid cytology samples

Abstract: Studies of cervical cancer (CC) have reported that microRNA-16-1 (miR-16-1), which is an oncomiR, is increased in the tissues and cell lines of CC. The aim of the present study was to investigate the association of miRNA-16-1 expression level with squamous cell carcinoma (SCC), the presence of squamous intraepithelial lesions (SIL) and the integration of high-risk human papillomavirus (HR-HPV) DNA. The current study analyzed 80 samples obtained from women by liquid-based cytology, which revealed that 20 were n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…The expression of miR-16-1 increased with the progression of the SIL. The expression of miR-16-1 in patients with HSIL was significantly higher than that in normal patients [6]. Nevertheless, when the expression level of miR16-1 in LSIL was compared with that in normal conditions a slight increase was identified, but it was not statistically significant.…”
Section: Dysregulation Of Mirnas Expression In Silmentioning
confidence: 70%
See 4 more Smart Citations
“…The expression of miR-16-1 increased with the progression of the SIL. The expression of miR-16-1 in patients with HSIL was significantly higher than that in normal patients [6]. Nevertheless, when the expression level of miR16-1 in LSIL was compared with that in normal conditions a slight increase was identified, but it was not statistically significant.…”
Section: Dysregulation Of Mirnas Expression In Silmentioning
confidence: 70%
“…In order to recognize the role of miRNAs in the initiation and early progression of cervical cancer, multiple research studies using HSIL and LSIL samples were performed [6,13,[31][32][33][34][35]. They consistently concluded that dysregulation of miRNAs' expression could explain the progression of SIL from normal cervical tissue.…”
Section: Dysregulation Of Mirnas Expression In Silmentioning
confidence: 99%
See 3 more Smart Citations